(untitled) (Modern education and development, 2024)
Bolani hayot tarzi, oilada qanday yashashi, oiladagi muhut ota ona munosabati bola tarbiyasi bolaning yoshlik va o’smirlik paytidagi psixologik jarayonlar kabi jarayonlar doimiy ravishda ko’pchilikni qiziqtirib kelgan. Ushbu maqolada bola psixologiyasi uchun ilmiyjihatdan olib borilgan tadqiqotlar haqida ma’lumotlar berilgan. Такие процессы, как образ ^жизни ребенка, как он живет в семье, атмосфера в семье, взаимоотношения родителей и детей, психологические процессы ребенка в период его юношеского и подросткового возраста вызывают постоянный интерес у многих людей. В данной статье представлена информация о научно проведенных исследованиях в области детской психологии. Processes such as the child’s lifestyle, how he lives in the family, the atmosphere in the family, the relationship between parents and children, the psychological processes of the child during his youth and adolescence are of constant interest to many people. This article provides information about scientifically conducted research in the field of child psychology.